Social innovation and territorial democratization: the civic-political approach of participatory budgeting in Pereira, Colombia (Revista Iberoamericana de Estudios Municipales, 2024)
This article analyzes social innovation (SI) approaches in the participatory budgeting of Pereira, Colombia (2016-2019), through a qualitative case study. Based on interviews, observations, and theoretical-empirical contrasts, a hybrid “civic-political” approach is identified, characterized by territorialized community agency, strategic conflict management, and impact on political culture and public management. The study concludes that this approach constitutes a “democratic innovation” with the potential to democratize local governance, although it faces challenges in sustainability and integration with long-term planning. The research provides evidence on the plurality of SI and its role in transforming territorial power relations, discussing implications for strengthening democracy and governance in the Global South.
Keywords: social innovation; participatory budgeting; civic-political approach; territorial democracy; community agency